Magnetic exposure using Samarium Cobalt (SmCO5) increased proliferation and stemness of human Umbilical Cord Mesenchymal Stem Cells (hUC-MSCs) - Abdul Hamid, Haslinda; Ramasamy, Rajesh; Mustafa, Mohd Kamarulzaki; Sarmadi, Vahid Hosseinpour; Miskon, Azizi (Nature Publishing Group, 2022)
Despite the extensive reports on the potential hazard of magnetic field (MF) exposures on humans, there are also concurrently reported on the improved proliferative property of stem cells at optimum exposure. However, the effect on mesenchymal stem cells (MSCs) remains unknown. Therefore, we aimed to investigate the impact of induced static MF (SMF) on human umbilical cord-derived mesenchymal stem cells (hUC-MSCs) using Samarium Cobalt (SmCO5). At passage 3, hUC-MSCs (1 × 104) were exposed to 21.6 mT SMF by a direct exposure (DE) showed a significantly higher cell count (p < 0.05) in the growth kinetics assays with the shortest population doubling time relative to indirect exposure and negative control. The DE group was committed into the cell cycle with increased S phase (55.18 ± 1.38%) and G2/M phase (21.75 ± 1.38%) relative to the NC group [S-phase (13.54 ± 2.73%); G2/M phase (8.36 ± 0.28%)]. Although no significant changes were observed in the immunophenotype, the DE group showed an elevated expression of pluripotency-associated markers (OCT4, SOX2, NANOG, and REX1). These results suggest that the MFs could potentially induce proliferation of MSCs, a promising approach to promote stem cells propagation for clinical therapy and research without compromising the stemness of hUC-MSCs.